Electronegative Low-density Lipoprotein Increases Coronary Artery Disease Risk in Uremia Patients on Maintenance Hemodialysis. Issue 2 (January 2016) - Chang, Chiz-Tzung; Wang, Guei-Jane; Kuo, Chin-Chi; Hsieh, Ju-Yi; Lee, An-Sean; Chang, Chia-Ming; Wang, Chun-Cheng; Shen, Ming-Yi; Huang, Chiu-Ching; Sawamura, Tatsuya; Yang, Chao-Yuh; Stancel, Nicole; et al.
Abstract : Abstract: Electronegative low-density lipoprotein (LDL) is a recognized factor in the pathogenesis of coronary artery disease (CAD) in the general population, but its role in the development of CAD in uremia patients is unknown. L5 is the most electronegative subfraction of LDL isolated from human plasma. In this study, we examined the distribution of L5 (L5%) and its association with CAD risk in uremia patients. The LDL of 39 uremia patients on maintenance hemodialysis and 21 healthy controls was separated into 5 subfractions, L1–L5, with increasing electronegativity. We compared the distribution and composition of plasma L5 between uremia patients and controls, examined the association between plasma L5% and CAD risk in uremia patients, and studied the effects of L5 from uremia patients on endothelial function. Compared to controls, uremia patients had significantly increased L5% ( P  < 0.001) and L5 that was rich in apolipoprotein C3 and triglycerides. L5% was significantly higher in uremia patients with CAD (n = 10) than in those without CAD (n = 29) ( P  < 0.05). Independent of other major CAD risk factors, the adjusted odds ratio for CAD was 1.88 per percent increase in plasma L5% (95% CI, 1.01–3.53), with a near-linear dose–response relationship. Compared with controls, uremia patients had decreased flow-mediated vascular dilatation. In ex vivo studies with preconstricted rat thoracic aortic rings, L5 from uremia patients inhibited acetylcholine-induced relaxation. In cultured human endothelial cells, L5 inhibited endothelial nitric oxide synthase activation and induced endothelial dysfunction. Our findings suggest that elevated plasma L5% may induce endothelial dysfunction and play an important role in the increased risk of CAD in uremia patients. Abstract : Supplemental Digital Content is available in the text